Inventarisasi Tumbuhan Survival Pada Ketinggian Yang Berbeda Pada Jalur Diklatsar Tlogodlingo Kecamatan Tawangmangu, Karanganyar. - Kustiari, Meilina; , Triastuti Rahayu, S.Si, M.Si (2015)
Education and Basic Training (DIKLATSAR) is an activity that have purpose to train participants to be more loving nature, nurture, and protect the nature. One of the materials in Education and Basic Training is survival. The part of survival material is the knowledge of wild plants that good and safe for consumption. The lack of knowledge about the plant species at Tlogodlingo will complicate the participants to know the types and benefits of that plant. The purpose of this study is to know the species, benefits and inventory survival plant around of the DIKLATSAR track at Tlogodlingo Tawangmangu Karanganyar at an altitude of 1.700 m.dpl, 1.850 m.dpl and 2.000 m.dpl. The method of this research is exploration and description of plants by observed morphological and described with exploring areas that have been agreed for the benefit of inventory. The data obtained are 12 orders, 14 family includes 17 species of plants scattered survival at three heights along the path Diklatsar. At an altitude of 1,700 m.dpl found 8 family includes 11 species, 1,850 m.dpl found 6 family includes 7 species, and 2,000 m.dpl 3 family includes 3 species.